Levels of VCAM-1 and ICAM-1 in serum of active and inactive Systemic Lupus Erythematosus patients as biochemical markers for risk of cardiovascular disease - Khammas, Hajer W.; Abdulhadi, Ghid H.; Munshid, Mohammad H. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Cardiovascular complications represent one of the consequences of chronic autoimmune diseases such as Systemic Lupus Erythematosus (SLE), which has significant rates of morbidity and mortality. Dyslipidemia can be brought on by steroid medications, which are frequently given to SLE patients and are considered to be one of the major risk factors for cardiovascular diseases. Objectives: This study attempted to investigate a potential association between circulating vascular cell adhesion molecule 1 (VCAM-1) and intercellular adhesion molecule 1 (ICAM-1) as risk factors for atherosclerosis and their relationship to cardiovascular risk. Patients and methods: A total of 100 patients and 50 apparently healthy controls were included in the study. All patients were from the Department of Rheumatology, Baghdad Hospital / Medical City during the period from 1 December 2021 to 1 March 2022 who were all treated with antimalarial drugs as immunosuppressants such as chloroquine (CQ) or hydroxychloroquine HCQ). They were divided according to the SLE disease activity index 2000 (SLEDAI-2K) into the active group (SLEDAI ≥ 10) and the inactive group (SLEDAI). Results: Serum VCAM and ICAM were significantly high in all study groups of SLE patients. The VCAM mean ± SD were (271.9±63.90), (247.9±82.92) and (97.7±24.69) in the active, inactive controls respectively. The ICAM mean ± SD were (3.1±0.91), (2.7±0.79) and (1.8±0.22) in the active, inactive and controls respectively. The values have increased gradually with increasing disease activity. The area under curve (AUC) of ICAM and VCAM were (0.802), (0.776) in active SLE patients and (0.858), (0.674) in inactive SLE patients. However, the AUC of VCAM and ICAM in active group were the highest. Conclusion: In SLE patients, VCAM-1 and ICAM-1 serum levels may operate as disease detection and severity differentiation indicators, and they may be linked to the number of coronary lesions in people at risk of developing CVD. Received: Aug.,2022 Accepted: Sept., 2022 Published: April 2023